Monocyte activation in early onset rheumatoid arthritis. Issue 7 (July 1990) - Fujii, I; Shingu, M; Nobunaga, M
Abstract : Monocytes from peripheral blood and synovial fluid of patients with definite and classic rheumatoid arthritis spontaneously produced significantly greater amounts of prostaglandin E2 (PGE2), leukotriene B4 (LTB4), and interleukin-1 beta (IL-1 beta) than samples of peripheral blood from normal controls. Peripheral blood monocytes from patients with rheumatoid arthritis produced significantly greater amounts of PGE2 than control samples when stimulated with lipopolysaccharide. There were no significant differences in the spontaneous release of superoxide or N-acetyl-beta-D-glucosaminidase by peripheral blood monocytes between patients and healthy controls. Both stimulated and unstimulated peripheral blood monocytes from patients with definite or classic rheumatoid arthritis produced significantly greater amounts of PGE2 than samples from normal controls. This was true, regardless of the stage of disease and the presence or absence of roentgenological joint abnormalities. Amounts of N-acetyl-beta-D-glucosaminidase released by peripheral blood monocytes from patients correlated positively with the erythrocyte sedimentation rate (ESR) and negatively with duration of disease. Amounts of IL-1 beta and N-acetyl-beta-D-glucosaminidase released from the peripheral blood monocytes of patients who had had their disease for less than one year were significantly higher than those of normal controls. There were no significant correlations between the types of treatment and the amounts of PGE2, LTB4, IL-1 beta or N-acetyl-beta-D-glucosaminidase released by peripheral blood monocytes in patients with rheumatoid arthritis. The findings suggest that monocytes are activated in patients with rheumatoid arthritis both at the onset of disease and during its chronic phase, and that they produce large amounts of mediators which may have a role in the induction and extension of the inflammatory process which leads to tissue damage.